(untitled) (The International Journal for Scientific Research, 2026)
This study aims to analyze the impact of climate change on groundwater and surface water resources in the Asir region, one of the most climatically sensitive areas in Saudi Arabia due to its strong dependence on seasonal rainfall and its diverse topography. The study highlights that the world is experiencing “rapid climatic changes that represent one of the most significant environmental challenges,” which have disrupted the global water balance—an effect clearly reflected in semi‑arid mountainous environments such as Asir. Climatic data indicate that the region has undergone substantial rainfall variability and a continuous rise in temperature, leading to increased evaporation rates and reduced groundwater recharge. The literature confirms that “climatic changes have led to a decline in natural recharge rates of aquifers.” Through the analysis of CHIRPS and ERA5 datasets, along with NDVI and SPI maps, the study shows that the years 1999 and 2024 exhibited marked differences in temperature and evaporation. Temperatures in 2024 exceeded 30°C during summer, while the SPI drought index recorded widespread negative values, particularly in inland areas, resulting in reduced surface runoff and declining water storage in dams and wells. Vegetation maps also revealed a noticeable decrease in biomass in areas experiencing severe drought, reflecting the impact of water stress on local ecosystems. The study underscores the critical role of topography in shaping rainfall distribution and runoff patterns, with the western highlands receiving the largest share of precipitation, while the eastern areas suffer from chronic aridity. It also highlights the importance of dams in regulating runoff and enhancing groundwater recharge, such as King Fahd Dam, which “contributed to improving groundwater recharge” according to local studies. Additionally, the study discusses the effects of drought on shallow wells and agriculture, noting that rainfall variability can lead to “the complete drying of some wells” and a decline in agricultural productivity. The study proposes several adaptation strategies, including improving irrigation efficiency, expanding rainwater‑harvesting systems through earthen barriers and micro‑catchments, and enhancing vegetation cover as a natural interception mechanism that reduces runoff velocity and increases infiltration. These measures align with Saudi Vision 2030 objectives to strengthen water security and promote sustainable natural‑resource management.